(3MGTjI Ydi QSGdI GdESJUMGHs - (3eMeO cGXe GdWhSi GdNQGSGfi GdgQhis; (3eQJVj Hf eMeO Gejf GdORahdj GdCfUGQj,J (B1281 (3g` s
(3ChdgG (B:s
(3CeG HYO ajbhd GdYHO GdCKe eMeO cGXe dGJONd ai GdMSGH ZdJWgG s
(3BNQgG (B:s
(3ai ebOeI GdGHJdGA MjK dGZjQGNJdGa ZjQ ehQO dGHJdGA adG jchf edMhXkG CUdkG ai GdeWGH s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdKGdKIs
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B201s
Keywords: (3abg GdePGgH GdCNQis